Phylogenetic relationships of some populations of edible nest swiftlet Aerodramus fuciphagus (Thunberg, 1812) on islands and mainland in Vietnam - Loan, Ho Thi; Son, Nguyen Giang; The, Dang Tat; Hung Son, Nguyen Lan (Academia Journal of Biology, 2015)
Edible-nest Swiftlets (A. fuciphagus) create nests using their solidified saliva. The nests have long been harvested because of their high economic value. This research addresses the phylogenetic relationships of several bird populations in Vietnam based on a portion of the cytochrome b gene with 606bp in length. Phylogenetic analyses show that populations inhabiting islands and mainland belong to different subspecies of A. fuciphagus. Wild swiftlets on islands are assigned to subspecies A. f. germani, while house swiftlets (birds on mainland) are recovered as A. f. amechanus with mean genetic divergence of 1.9%. There are some specific sites for nucleotide substitutions between the two groups (group resident on islands and mainland, respectively): 36 (C-T), 93 (G-C), 96 (C-T), 117 (T-C), 306 (G-A), 468 (G-A), 489 (A-G), 531 (T-C). Our results suggest that the recently recorded house swiftlet populations (subspecies A. f. amechanus) in Vietnam are probably originated from the southern region of Southeast Asia. We recommend that future studies should include nuclear genes (chromosome genes) to evaluate cross-hybrid between the populations.